Factors associated with infertility among married women in Rajshahi City, Bangladesh: 10.55131/jphd/2022/200311 - Khatun, Nasrin; Mondal, Md Nazrul Islam; Islam, Md Rafiqul; Hossain, Md Kamal; Parvin, Mst Nadira; Hossen, Md Shamim; Haque, Nazrul; Karim, Md Rejaul; Islam, Md Shariful (Journal of Public Health and Development, 2022)
Infertility has become a growing problem among reproductive aged women in both developing and developed countries. Recent statistics indicate a significant number of married couples suffering from infertility and visiting infertility centers has increased in Bangladesh. Therefore, this study aims to identify the factors associated with infertility in Bangladeshi women. This is a retrospective study and data were collected from 450 reproductive aged women purposively using a structured questionnaire from an infertility center in Rajshahi City, Bangladesh. Univariate, bivariate and multivariate analyses were used to reach the objectives. The results revealed that most respondents (58.2%) were overweight and obese by measuring Body Mass Index (BMI). Age, age at first marriage, BMI, duration of contraceptive use, husband’s diabetes status, and husband’s drug addiction were found significantly associated with infertility. Infertility cases were found to be higher among women aged ≥30 years (OR: 10.16; 95% CI: 2.70-38.2; p <0.001). Overweight and obese women are 2.33 times more likely to be infertile compared to underweight women (OR: 2.33; 95% CI: 0.12-0.57; p <0.008). The couple who use the contraceptive for 2 years and above are around 2 times more likely to be infertile compared to those using it for months (OR: 1.99; 95% CI: 0.97-4.09; p <0.059). The women whose husbands use drugs are 5.51 times at higher risk to be infertile compared to those women whose husbands did not take drugs (OR: 5.51; 95% CI: 2.35-12.90; p <0.000). Thus, child expected couples should consider the aforesaid factors. As infertility has a complex relation with basic risk factors, the study findings may help the health policy researchers to address more underlying risk factors of infertility in their further studies. Moreover, these results could be carefully considered by the government and stakeholders to find effective interventions and solutions to the infertility problem in Bangladesh, especially in Rajshahi City, Bangladesh.